Outcome of Oral Steroids After Optical Internal Urethrotomy (OIU) In Comparison eith OIU Only (Bangladesh Journal of Urology, 2023)
Objectives: To evaluate the effects of Oral Steroid as Tablet Deflazacort(6mg)  in the prevention of recurrence of short segment anterior urethral stricture after optical internal urethrotomy compare with OIU only.Material and methods: This present Randomized clinical comparative study was designed to observe the efficacy of Oral  Steroid as Tablet Deflazacort (6mg)  after optical internal urethrotomy. All male patients of age between 18-45 years, who were diagnosed as short segment anterior urethral stricture(